Heavy Metal Uptake of Corn Irrigated with Human Urine - Horacio Sabejon Factura (International Journal of Advances in Applied Sciences, 2017)
Pit latrine (PL) is one of the most common disposal systems for human excreta in low-income countries but because it is a hole in the ground, infiltration of liquid effluent into the soil can continuously occur. Poor sanitation systems permit the spread of heavy metals in urine to water bodies especially the groundwater. This study investigated the accumulation of heavy metals in shoots of corn plants irrigated with urine. A pot experiment with corn was conducted under greenhouse conditions. Urine was diluted to 3:1 ratio (water and urine respectively) and was compared to control (water only). Using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), heavy metals such as Boron, Barium, Cobalt, Copper, Iron, Manganese, Nickel, Silicon, Strontium and Zinc were detected in shoots of all plants with contents ranging from 0.22 to 2,487.44 milligram (mg) per kilogram (kg). The higher amounts detected in urine irrigated plants than the control proved the presence of the metals in the urine. Reuse of urine will definitely benefit farmers while at the same time reduce the risk of heavy metal contamination in groundwater.